The competitiveness level of SMEs in Johor Bahru / Mohd Razis Sipon - Sipon, Mohd Razis (Faculty of Business and Management, 2015)
The purpose of this research is to identify the most significant variable to measure the competitiveness level of SMEs in Johor Bahru. There are three variable to measure the competitiveness level of SMEs that are human resource background, cost reduction, and use of technology which are the independent variables for this research. The research is being conducted towards the SMEs customer of Ministry of international trade (MITI) and SME Corp in Johor Bahru and more focus the SMEs that doing international activities. The information is gathered by distributed questionnaire to the SMEs business by using convenience sampling, that are 200 questionnaire are distributed to the respondent but only 150 of questionnaire of the respondent are answering the questionnaire. Their feedbacks on answering the questionnaire will be analyze and summarize by using the Statistical Package for Social Science (SPSS) version 19 and above. The result or the findings from this research shows that the three variable are the indicator to measure the competitiveness of SMEs in Johor Bahru. Thus, several suggestions and recommendations are being made in order to encourage the SMEs in Johor to be more competitiveness to compete locally or globally.